Immobilization and characterization of G51 keratinolytic enzymes with potential for wool processing - Iglesias, Martín Sebastián (2018)
Bacillus sp. G51 produces extracellular keratinases with potential for shrink-proofing of wool. Keratinases are proteases with autolytic activity which are restringing their industrial application in free form. Immobilization could contribute to a better control of their catalytic activity. Our aim was to immobilize and characterize G51 extracellular enzymes by cross-linking of enzyme aggregates (CLEA). G51 culture supernatant was used for CLEA with glutaraldehyde as cross-linking agent. G51 enzyme units (EU)/glutaraldehyde ratio was optimized, obtaining the best recovery of the proteolytic activity with the lowest ratio tested (8.4% with 3.5 EU/mlglu25%). CLEA-G51 thermal stability was higher (91 and 71% of residual activity after 1 h at 50 and 60°C, respectively) than that of free enzymes (40 and 5% residual activity under the same conditions). After 4 month-storage at room temperature, the free and immobilized enzymes kept 20 and 80% of residual proteolytic activity, respectively. This improvement of storage stability suggests that immobilization could prevent G51-keratinase autolysis and loss of activity. More than 60% of the proteolytic activity was preserved in the 3rd use, and it gradually diminished to 30% after seven re-uses. CLEA-G51 enzymes retained its wool keratinolytic activity (0.06 EU/ml), which is essential for wool shrink-proofing. CLEA-G51 operational and storage advantages could be valuable for industrial applications. Particularly, increased molecular size of immobilized G51 keratinases could avoid their diffusion into the wool fiber, allowing wool treatments with higher enzyme concentrations and without excessive degradation.